Mutations of FUS gene in sporadic amyotrophic lateral sclerosis. Issue 3 (26th October 2009) - Corrado, Lucia; Del Bo, Roberto; Castellotti, Barbara; Ratti, Antonia; Cereda, Cristina; Penco, Silvana; Sorarù, Gianni; Carlomagno, Yari; Ghezzi, Serena; Pensato, Viviana; Colombrita, Claudia; Gagliardi, Stella; et al.
Abstract : Background: Mutations in the FUS gene have recently been discovered to be a major cause of familial amyotrophic lateral sclerosis (FALS). Objective: To determine the identity and frequency of FUS gene mutations in a large cohort of Italian patients enriched in sporadic cases (SALS). Methods: Exons 5, 6, 14 and 15 of the FUS gene were screened for mutations in 1009 patients (45 FALS and 964 SALS). The genetic analysis was extended to the entire coding sequence of FUS in all the FALS and 293 of the SALS patients. Results: Seven missense mutations (p.G191S, p.R216C, p.G225V, p.G230C, p.R234C, p.G507D and p.R521C) were identified in nine patients (seven SALS and two FALS), and none in 500 healthy Italian controls. All mutations are novel except for the p.R521C mutation identified in one SALS and one FALS case. Both patients showed a similar unusual presentation, with proximal, mostly symmetrical, upper limb weakness, with neck and axial involvement. With the exception of p.G507D and p.R521C, the mutations identified in SALS patients are all localised in the glycine-rich region encoded by exon 6. In addition, eight different in-frame deletions in two polyglycine motifs were detected, the frequency of which was not significantly different in patients and controls. Conclusions: The results show that FUS missense mutations are present in 0.7% of Italian SALS cases, and confirm the previous mutational frequency reported in FALS (4.4%). An unusual proximal and axial clinical presentation seems to be associated with the presence of the p.R521C mutation.